Reconstruction of Maxillofacial Defects: Current Strategies and Future Innovations - Aisha Faraz ,Madiha Khan , Sufyan Ahmed, Haris Khan, Quratulain, Asna Khalid, Farah Naz Tahir (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Maxillofacial defects resulting from trauma, tumor resection, or congenital anomalies require complex reconstruction strategies that restore both function and aesthetics. Conventional techniques often involve autologous bone grafting or free flap transfers, which are associated with donor site morbidity and extended surgical time. Regenerative approaches incorporating autologous biologics such as Platelet-Rich Fibrin (PRF)* have demonstrated promising results in enhancing tissue healing and regeneration.